2017
DOI: 10.1186/s13256-017-1508-8
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive therapy for manic state with mixed and psychotic features in a teenager with bipolar disorder and comorbid episodic obsessive–compulsive disorder: a case report

Abstract: BackgroundComorbidity of bipolar disorder and obsessive–compulsive disorder is common in adolescence. Obsessive–compulsive disorder symptoms may be episodic and secondary to alterations in mood, and display specific features. Management of pediatric bipolar disorder-obsessive–compulsive disorder is challenging, as pharmacotherapy of obsessive–compulsive disorder may induce or exacerbate manic episodes and there is limited evidence of treatment efficacy. Electroconvulsive therapy is sparsely used in children an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…The primary diagnostic indication for ECT in adolescents is often severe mood disorder 23,77,78 . The efficacy of ECT has been demonstrated in cases of treatment-resistant mood disorders in adolescents, particularly unipolar depression and bipolar disorder, 24,79–83 whereas evidence for ECT in the treatment of acute mania is limited 25,26,84 . Cohen et al 85 reported 100% remission in 10 patients aged 14 to 19 years with depression and 75% remission in a sample of 4 patients with bipolar manic episodes, based on clinical impression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary diagnostic indication for ECT in adolescents is often severe mood disorder 23,77,78 . The efficacy of ECT has been demonstrated in cases of treatment-resistant mood disorders in adolescents, particularly unipolar depression and bipolar disorder, 24,79–83 whereas evidence for ECT in the treatment of acute mania is limited 25,26,84 . Cohen et al 85 reported 100% remission in 10 patients aged 14 to 19 years with depression and 75% remission in a sample of 4 patients with bipolar manic episodes, based on clinical impression.…”
Section: Resultsmentioning
confidence: 99%
“…23,77,78 The efficacy of ECT has been demonstrated in cases of treatment-resistant mood disorders in adolescents, particularly unipolar depression and bipolar disorder, 24,[79][80][81][82][83] whereas evidence for ECT in the treatment of acute mania is Open, prospective study 10 patients, aged 14-18 y limited. 25,26,84 Cohen et al 85 reported 100% remission in 10 patients aged 14 to 19 years with depression and 75% remission in a sample of 4 patients with bipolar manic episodes, based on clinical impression. Similar results were found by Walter and Rey 86 in 42 patients aged 14 to 17 years (51% across different diagnoses and 100% in mania) and by Strober et al 27 who found 60% complete and 40% partial remission in a sample of 10 patients aged 13 to 17 years with major depression and bipolar depression, when measured by the Hamilton Depression Rating Scale after 1 week.…”
Section: Evidence For Ect In Mood Disordersmentioning
confidence: 99%
“…No acompanhamento pós-alta, manteve estabilidade do quadro e uso regular das medicações, com retorno completo da funcionalidade. Rask et al (2017) apresentaram o caso de uma paciente de 16 anos que se apresentou com humor deprimido, irritabilidade e aumento de sintomas de transtorno obsessivo-compulsivo, que foram inicialmente interpretados no contexto de estresse agudo secundário à imigração. Ela havia sido diagnosticada com transtorno bipolar e transtorno obsessivo-compulsivo em seu país natal, mas apresentava dificuldades em explicar seu histórico psiquiátrico anterior.…”
Section: Discussionunclassified
“…Os estudos envolvendo estimulação cerebral profunda e ECT, apesar de limitados, apresentam resultados relevantes sobre potenciais estratégias terapêuticas. [34,35].…”
Section: Discussionunclassified
“…Um segundo relato de caso reportou resposta satisfatória com o uso de Eletroconvulsoterapia (ECT) em paciente com SOC e em episódio misto com sintomas psicóticos. O ECT foi iniciado após 8 semanas de internação e farmacoterapia [35]. https://doi.org/10.25118/2763-9037.2022.v12.295…”
Section: Outras Alternativas Terapêuticas Na Comorbidadeunclassified